Anionic Cerium Oxide Nanoparticles Protect Plant Photosynthesis from Abiotic Stress by Scavenging Reactive Oxygen Species - Wu, Honghong; Tito, Nicholas; Giraldo, Juan P (ACS nano, 2017)
Plant abiotic stress leads to accumulation of reactive oxygen species (ROS) and a consequent decrease in photosynthetic performance. We demonstrate that a plant nanobionics approach of localizing negatively charged, sub-11 nm, spherical cerium oxide nanoparticles (nanoceria) inside chloroplasts in vivo augments ROS scavenging and photosynthesis of Arabidopsis thaliana plants under excess light (2000 μmol m–2 s–1, 1.5 h), heat (35 °C, 2.5 h), and dark chilling (4 °C, 5 days). Poly(acrylic acid) nanoceria (PNC) with a hydrodynamic diameter (10.3 nm)lower than the maximum plant cell wall porosityand negative ζ-potential (−16.9 mV) exhibit significantly higher colocalization (46%) with chloroplasts in leaf mesophyll cells than aminated nanoceria (ANC) (27%) of similar size (12.6 nm) but positive charge (9.7 mV). Nanoceria are transported into chloroplasts via nonendocytic pathways, influenced by the electrochemical gradient of the plasma membrane potential. PNC with a low Ce3+/Ce4+ ratio (35.0%) reduce leaf ROS levels by 52%, including hydrogen peroxide, superoxide anion, and hydroxyl radicals. For the latter ROS, there is no known plant enzyme scavenger. Plants embedded with these PNC that were exposed to abiotic stress exhibit an increase up to 19% in quantum yield of photosystem II, 67% in carbon assimilation rates, and 61% in Rubisco carboxylation rates relative to plants without nanoparticles. In contrast, PNC with high Ce3+/Ce4+ ratio (60.8%) increase overall leaf ROS levels and do not protect photosynthesis from oxidative damage during abiotic stress. This study demonstrates that anionic, spherical, sub-11 nm PNC with low Ce3+/Ce4+ ratio can act as a tool to study the impact of oxidative stress on plant photosynthesis and to protect plants from abiotic stress.